(3cJGH aj GdOYGAs - (3eLghds
(3ChdgG (B:s
(3ChdgG(B: (3haj cd JGHhJ SHYhf Cda YbQH ef GdfGQ, hYdi cd JGHhJ SHYhf Gda TLQI ef GdRbhe, hJMJ cd TLQI SHYhf Cda hJO ef GdfGQs
(3BNQgG (B:s
(3BNQgG(B: (3aGdMQU deGPG hEf cGf GdNda ef Gddg YR hLd, (B.. (3dePG hEf cGfJ GdYbhHI ef Gddg JYGdi, aGdeYUjI deGPG hEf cGf GdehJ MbGs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs